Primary antiphospholipid syndrome presenting with unilateral renal infarction and C4d-positive cortical necrosis: a case report with a pooled analysis of 24 cases - Zhang, Jing; Zhang, Lina; Li, Sheng-Guang; Li, Ji; Zou, Yadan; Long, Ting; Yu, Ruohan; Zhang, Yanfeng (Frontiers in Immunology, 2026)
Primary antiphospholipid syndrome (APS) is an autoimmune thrombophilic disorder characterized by recurrent venous or arterial thrombosis and/or pregnancy morbidity in the presence of persistent antiphospholipid antibodies (aPL). Renal involvement in APS is heterogeneous and may include renal artery thrombosis, renal vein thrombosis, thrombotic microangiopathy, and chronic APS nephropathy. However, unilateral renal infarction as the first and isolated manifestation of primary APS is exceedingly rare. We report a 23-year-old man with no prior medical history who presented with fever, flank pain, and hematuria and was found to have unilateral left renal infarction with cortical necrosis. Imaging showed a slender mid-to-distal segmental defect in the left renal artery with markedly reduced perfusion and extensive cortical non-enhancement. Laboratory testing revealed persistent lupus anticoagulant (LA) and high-titer anticardiolipin antibody (aCL) IgG, fulfilling criteria for primary APS. A percutaneous renal biopsy, performed to clarify the mechanism of injury and exclude immune-complex glomerulonephritis or primary vasculitis, demonstrated diffuse cortical necrosis with fibrin-rich thrombi in small arteries and intense C4d deposition along glomerular capillary and small arterial walls, without immune-complex deposition. We also conducted a pooled analysis of 24 APS cases with renal infarction identified in the literature. Most involved arterial thrombosis, often in young patients, with variable outcomes depending on laterality and timeliness of anticoagulation. Our case underscores several key teaching points (1): APS should be considered in young patients with unexplained renal infarction (2); transient positivity of multiple autoantibodies (including dsDNA, ANCA, and anti-GBM) may be misleading and requires cautious interpretation with repeat testing (3); C4d deposition supports complement-mediated thrombosis as a pathophysiologic mechanism in APS nephropathy; and (4) early diagnosis and anticoagulation are crucial for a favorable outcome.